Taxonomic and physioecological significance of the floral surface micromorphology of Vanda helvola and vanda dearei (orchidaceae) - Besi, Edward Entalai; Ling, Swee Chie; Rusea, Go (Penerbit UMT, 2021)
The Vanda orchid is appreciated for its large, beautiful, scented flowers. Anatomical enumeration of the most compatible Vanda species holds interesting and under-investigated aspects. We conducted an in-depth investigation into the floral-surface micromorphology of V. helvola and V. dearei, and assessed the significance in taxonomic delimitation using scanning electron microscopy (SEM) to feasibly answer questions on the reported dubious origins of certain Vanda species and hybrids. Floral trichomes, including papillae structures, stomata, epicuticular ornamentation and waxes, were enumerated and compared between the selected species. Findings based on the photomicrographs revealed that V. helvola and V. dearei were comparable based on the diversity and dissemination of trichomes, stomata and epicuticular ornamentation. Noteworthy was the heterogeneous occurrence of distinguishing barrel-shaped glandular trichomes with aperture, which might also function as nectaries, and branched glandular and biseriate trichomes on the labellum of V. helvola, but was absent in V. dearei. In contrast, an aggregation of conical papillae occurred on the spur of V. dearei, but lacking in V. helvola. We also employed SEM observations to understand the role of surface microstructures in physio-ecological functions. The glandular trichomes and stomata were presumed to be secretory structures for the unique scents of V. helvola and V. dearei.